Predictors of age at diagnosis in autism spectrum disorders: the use of multiple regression analyses and a classification tree on a clinical sample - Hrdlicka, Michal; Urbanek, Tomas; Rotreklova, Adela; Kultova, Aneta; Valek, Ondrej; Dudova, Iva (European child & adolescent psychiatry, 2024)
The increasing prevalence of autism spectrum disorders (ASD) has led to worldwide interest in factors influencing the age of ASD diagnosis. Parents or caregivers of 237 ASD children (193 boys, 44 girls) diagnosed using the Autism Diagnostic Observation Schedule (ADOS) completed a simple descriptive questionnaire. The data were analyzed using the variable-centered multiple regression analysis and the person-centered classification tree method. We believed that the concurrent use of these two methods could produce robust results. The mean age at diagnosis was 5.8 ± 2.2 years (median 5.3 years). Younger ages for ASD diagnosis were predicted (using multiple regression analysis) by higher scores in the ADOS social domain, higher scores in ADOS restrictive and repetitive behaviors and interest domain, higher maternal education, and the shared household of parents. Using the classification tree method, the subgroup with the lowest mean age at diagnosis were children, in whom the summation of ADOS communication and social domain scores was ≥ 17, and paternal age at the delivery was ≥ 29 years. In contrast, the subgroup with the oldest mean age at diagnosis included children with summed ADOS communication and social domain scores < 17 and maternal education at the elementary school level. The severity of autism and maternal education played a significant role in both types of data analysis focused on age at diagnosis.
Keywords: Regression Analysis; pervazivní vývojové poruchy u dětí; Male; Maternal education; Age at diagnosis; Autism spectrum disorders; Autism Spectrum Disorder; Autistic Disorder; předškolní dítě; Humans; Child, Preschool; Shared household; Communication; mužské pohlaví; komunikace; Female; regresní analýza; ženské pohlaví; Child Development Disorders, Pervasive; Paternal age; autistická porucha; ADOS; Adult; lidé; dítě; dospělí; poruchy autistického spektra; Child